Marked decline of sudden mass fatality events in New Zealand 1900 to 2015: the basic epidemiology. (28th February 2017) - Wilson, Nick; Morales, Adrienne; Guy, Nicola; Thomson, George
Abstract: Objective: To describe the basic epidemiology of sudden mass fatality events for the 1900 to 2015 period in New Zealand (NZ). Methods: Official lists and internet searches were used to identify the events. Events were categorised, rates calculated and time trends analysed. Results: A total of 56 sudden mass fatality events with 10 or more fatalities between 1900 and 2015 in NZ were identified. There were 1, 896 deaths in total, with the worst event being the Hawke's Bay earthquake (258 deaths). Events were classified as transportation‐related (64%), natural causes (11%), industrial (9%), war (9%) and infrastructure (5%). There were marked declines in the rate of events per person‐years of exposure and the associated mortality rate (both p <0.0001). Knowledge gaps were identified around: i) the basic epidemiology, e.g. non‐fatal injuries and numbers of survivors; ii) the role of subsequent official inquiries in guiding preventive measures; and iii) the likely cost‐effectiveness of measures to prevent harm from such events. Conclusions: The occurrence and health burden of sudden mass fatality events have markedly declined in NZ over time. Implications for public health: There remains large scope for addressing the knowledge gaps in the basic epidemiology and societal responses to these events to guide primary prevention and appropriate disaster response.